Pembelajaran Toleransi dan Kearifan Lokal pada Masyarakat Plural: Belajar dari Penyelesaian Konflik Sosial di Poso - Asep Mahpudz (Proceedings Series on Social Sciences & Humanities, 2023)
This paper aims to analyze the application of local wisdom values and tolerance as good lessons for conflict resolution in post-conflict Poso society. In the Poso conflict, religion was not the main cause of the conflict. The existence of rivalry between elements of society in fighting over political and bureaucratic economic resources became the root of the problem of conflict in Poso. The reason religion becomes a support for political legitimacy and identity to commit violence against others. The potential for conflict in the Poso community can be reduced through the application of local wisdom values and tolerance values. Learning about the values of local wisdom and tolerance is an important factor in reconciliation to strengthen the solidarity of the people who were divided during the conflict. The cultural values of Sintuwu Maroso as the local wisdom of the people in Poso and the application of tolerance values in society are important to continue to develop so that they can reduce conflict and can become an adhesive for peaceful life in Poso.